Political Connections and Debt Access: The Case of Tunisian Firms - Bencheikh, Fayrouz; Taktak, Neila Boulila (International Journal of Economics and Financial Issues, 2017)
The purpose of this paper is to study the effect of political connections on debt access in the case of Tunisian firms before and after the 2011 uprising. The results show that the impact of political connections on debt access differs according to three criteria: Firstly, according to debt maturity, secondly according to the degree of political connections, and finally according to the sub-period studied. Keywords: Debt Access, Political Connections, Tunisia JEL Classifications: G30, G31